2019
DOI: 10.1021/acs.jpcc.9b07756
|View full text |Cite
|
Sign up to set email alerts
|

Direct Link between Structure, Dynamics, and Thermodynamics in Molten Salts

Abstract: The strongly increased use of molten salts in the energy industry necessitates knowledge of their physicochemical properties on a microscopic scale to guide the development of new technology. Here, we focus on the eutectic LiCl−KCl mixture and unravel the links between structure, dynamics, and thermodynamics and investigate both mixing and temperature effects. In the mixture, for K−Cl, an elongation of the ionic bond length is accompanied by faster ion dynamics and lower Gibbs energy of activation; the opposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 55 publications
5
19
0
Order By: Relevance
“…Simulations including explicit polarizability of the ions effectively model three body interactions, going beyond the pair potential approximation underlying classical force fields 28 . It has been shown that the model predicts physicochemical properties accurately over a wide range of temperatures for the gas, liquid, and solid phases, compared to both other force fields and experimental data [16][17][18]29 .…”
mentioning
confidence: 99%
“…Simulations including explicit polarizability of the ions effectively model three body interactions, going beyond the pair potential approximation underlying classical force fields 28 . It has been shown that the model predicts physicochemical properties accurately over a wide range of temperatures for the gas, liquid, and solid phases, compared to both other force fields and experimental data [16][17][18]29 .…”
mentioning
confidence: 99%
“…The force field performs well for molten salts, both pure alkali halides and mixtures, with improved results for equilibrium and dynamical properties in comparison to both experiments and other force fields. 6,16,17 In contrast to molecular mechanics, ab initio quantum chemistry calculations are in general considered to provide the most accurate approach to calculate physicochemical properties via computer simulations. Melting points have been determined using ab initio Molecular Dynamics (MD), however this is computationally demanding, in particular for strongly ionic substances, 18 and the accuracy is limited by sampling and system size convergence.…”
mentioning
confidence: 99%
“…In our latest contribution we showed that our polarisable force field is indeed able to accurately predict physicochemical properties, such as the conductivity, of such a mixture. 17 As an alternative to using polarisable models, Leontyev and Stuchebrukhov [22][23][24][25] introduced ions with effective charges that are scaled down in order to mimic the electronic dielectric screening in condensed matter. Such models work in conjunction with other effective-charge empirical models such as popular water models.…”
mentioning
confidence: 99%
See 2 more Smart Citations